2011
DOI: 10.1186/1476-511x-10-166
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles induced cloudy swelling to hydropic degeneration, cytoplasmic hyaline vacuolation, polymorphism, binucleation, karyopyknosis, karyolysis, karyorrhexis and necrosis in the liver

Abstract: BackgroundNanoparticles (NPs) can potentially cause adverse effects on organ, tissue, cellular, subcellular and protein levels due to their unusual physicochemical properties. Advances in nanotechnology have identified promising candidates for many biological and biomedical applications. The aim of the present study was to investigate the particle-size, dose and exposure duration effects of gold nanoparticles (GNPs) on the hepatic tissue in an attempt to cover and understand the toxicity and their potential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 19 publications
6
96
0
Order By: Relevance
“…15,16 In contrast, monodispersed Au NPs did not exert a higher acute effect compared to their agglomerates, when using pulmonary inflammation as a marker for toxicity after intratracheal instillation in rats. 17 Furthermore, the model organism Drosophila melanogaster showed DNA fragmentation and significant concentration-dependent and size-independent modulation of expression levels of the genes involved in stress stimuli (hsp70 and hsp83), DNA damage (p53) and apoptosis pathway (Dark, Dronc, and Dredd) upon ingestion of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In contrast, monodispersed Au NPs did not exert a higher acute effect compared to their agglomerates, when using pulmonary inflammation as a marker for toxicity after intratracheal instillation in rats. 17 Furthermore, the model organism Drosophila melanogaster showed DNA fragmentation and significant concentration-dependent and size-independent modulation of expression levels of the genes involved in stress stimuli (hsp70 and hsp83), DNA damage (p53) and apoptosis pathway (Dark, Dronc, and Dredd) upon ingestion of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Notes: Mass concentrations (0.1-100 µg/ml) were expressed as theoretically calculated number of au NPs ranging from 2.93×10 12 to 7.92×10 16 . In PBl (A and C) and raw264.7 (B and D), after 2 hours (A and B) and 24 hours (C and D) treatment, no statistically significant differences among the cytotoxicity of 5 nm and 15 nm au NPs were observed.…”
mentioning
confidence: 99%
“…[27][28][29][30][31][32] However, little attention has been paid to kidneys, which are particularly susceptible to xenobiotics due to their high blood supply and ability to concentrate toxins. Sereemaspun et al 33 demonstrated that GNPs were heavily taken up by kidney cells, causing nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of hepatocytes might be exhibited as a result of disturbances of membranes function, that could be confirmed by the accompanied leakage of lysosomal hydrolytic enzymes [22]. The hydropic degeneration is a result of ion and fluid homeostasis unbalance that lead to an increase in intracellular water [22]. The histological changes appearing in the kidney of adult and juvenile groups were pronounced in case of alum adjuvant.…”
Section: Discussionmentioning
confidence: 90%
“…Küpffer cells activation might indicate that nanoparticles activate the phagocytic activity of the sinusoidal cells by increasing the number of Küpffer cells to help in removing the accumulated nanoparticles [21]. The swelling of hepatocytes might be exhibited as a result of disturbances of membranes function, that could be confirmed by the accompanied leakage of lysosomal hydrolytic enzymes [22]. The hydropic degeneration is a result of ion and fluid homeostasis unbalance that lead to an increase in intracellular water [22].…”
Section: Discussionmentioning
confidence: 99%